Pernikahan Campuran dan Status Anak dalam Hukum Perdata Internasional - Anjani Anjani; Detriansya Detriansya; Putri Aprianti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This academic paper provides a comprehensive analysis of mixed marriages and the legal status of children within the context of Indonesian International Private Law. The study meticulously explores the formal definition of a mixed marriage, establishing it as a legal union between individuals of different citizenships, thereby subject to intersecting national legal systems. The research delves into the specific regulatory framework governing Mixed Marriages in Indonesia, with a critical examination of Law No. 1 of 1974 on Marriage and its implementing regulations. A significant portion of the analysis is dedicated to the intricate legal aspects concerning the child's status in a mixed marriage. This encompasses a detailed discussion on the child's citizenship, governed by the principle of ius sanguinis under Law No. 12 of 2006 on Citizenship, which creates potential for dual citizenship and subsequent legal complexities. The paper further investigates the fundamental rights and obligations of the child, affirming that these must be upheld irrespective of parental nationality, including the inalienable right to a legal identity, parental care, and formal education. Concurrently, the research outlines the concomitant parental obligations in a mixed marriage, which are paramount and include the provision of nurture, guidance, and comprehensive protection for the child's well-being. The study concludes with a critical evaluation of the practical implementation of these mixed marriage law aspects in Indonesia, identifying discernible gaps between statutory provisions and their real-world application. It underscores persistent challenges in juridical practice and administrative consistency, ultimately highlighting the ongoing pursuit of complete legal certainty for binational families navigating the Indonesian legal landscape.